Planned Misery of the Children in Al-Hol: Distancing as Bar to Rights and Consular Protection - Korhonen Outi; Halme-Tuomisaari Miia (Scientific Research Publishing, 2025)
Why are Western governments not retrieving detained minor nationals from Al-Hol’s purgatory-like conditions? This article shows, under international human rights law, that the status of detained children as rights bearers is uncontroversial, as is their right to positive protection. We raise issues from recent debates on the securitisation of geopolitics in the relationship between the Middle East and the West, to demonstrate that there is little randomness, accidental, or arbitrary in the detained children’s suffering. The suffering is a product of the socio-economic arrangement that characterises our prevailing world order—and that is connected to international human rights law’s “civilising mission”. We conclude by asking: How is the legitimacy of the human rights regime sustained despite fundamental inconsistencies and failures to realise its purpose?